Integrated carbon / carbon composite material crucible containing three layers of composite coatings
By designing a three-layer composite coating and a multi-layer structural prefabricated body on an integrated carbon/carbon composite crucible, the problem of poor bonding between the prefabricated body and the functional coating is solved, and the service life and performance of the crucible are improved.
Patent Information
- Application Number
- CN202411569371.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-03-14
AI Technical Summary
In the existing integrated carbon/carbon composite crucibles, the bonding of the prefabricated body and subsequent functional coatings is poor, which affects the service life of the crucible.
The three-layer composite coating design is adopted, including glass-carbon coating, pyrolytic carbon transition coating and yttrium oxide coating, combined with the design of a multi-layer structural prefabricated body to improve the combination effect of the crucible and functional coating.
It significantly improves the service life of the crucible, enhances the thermal stability and silicon corrosion resistance of the crucible, and ensures the purity of the molten silicon.
Smart Images

Figure CN119613153A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an integrated carbon / carbon composite material crucible containing three layers of composite coating, belonging to the technical field of thermal field components for single crystal silicon. Background Art
[0002] The single crystal silicon pulling furnace used in traditional single crystal silicon pulling is usually composed of a carbon / carbon crucible and a quartz crucible, that is, the quartz crucible is nested in the carbon / carbon crucible. The quartz crucible plays the role of carrying silicon materials to ensure the purity of silicon materials, while the carbon / carbon crucible plays the role of carrying the quartz crucible and providing strength support. The temperature inside the single crystal silicon pulling furnace is as high as 1500℃. The quartz crucible holding the silicon materials will have problems such as deformation and softening, and replacement is very frequent. About 1 carbon / carbon crucible will consume 12 to 18 quartz crucibles. In addition, the raw material quartz sand for the production of quartz crucibles is relatively scarce. In recent years, the rapid increase in the price of high-purity quartz sand and the imbalance between supply and demand have led to high crystal pulling costs.
[0003] Carbon / carbon composite materials are composite materials formed by carbon fiber or various carbon fabrics reinforced with carbon matrix. They have excellent properties such as low density, high specific strength, wear resistance, and high temperature resistance. They are currently widely used in aerospace, metallurgy, new energy and other fields. At present, researchers have proposed the use of "integrated carbon / carbon composite crucibles" to replace the traditional "combination of carbon / carbon crucibles and quartz crucibles". On the one hand, it can avoid the impact of the rapid rise in the price of high-purity quartz sand and reduce the material cost of crystal pulling. On the other hand, the integrated design can combine materials and performance into one, maximize its advantages, and further reduce product costs.
[0004] The integrated carbon / carbon composite crucible is formed by densifying the carbon fiber preform to form a carbon / carbon composite crucible body, and then preparing a high-performance coating on the inner surface of the carbon / carbon composite crucible body. For example, patent CN103102170A prepares SiC coating and Si3N4 coating on the inner surface of the carbon / carbon composite crucible body, which can significantly increase the number of times the crucible can be used and significantly improve its life. However, the surface of the Si3N4 coating is relatively rough and has a certain wettability to silicon. There is a risk of damaging the Si3N4 coating during the production process of single crystal silicon.
[0005] In addition, the carbon fiber preform is the blank for preparing carbon / carbon composite crucibles, which directly affects the service life of crucible products. The disclosed carbon fiber preform is usually prepared by laminating a layer unit consisting of a carbon fiber woven cloth / carbon fiber mesh layer combined with a carbon fiber filament winding layer. Although the carbon fiber preform has high mechanical strength and good shaping effect, due to the presence of the carbon fiber woven cloth on its inner surface, the surface roughness is low and the bonding with the subsequent functional coating is poor, which will greatly affect the service life of the crucible product. Summary of the invention
[0006] In view of the problem that the preform in the current integrated crucible has poor bonding with the subsequent functional coating, the present invention provides an integrated carbon / carbon composite material crucible containing three layers of composite coatings, wherein a glassy carbon coating, a pyrolytic carbon transition coating and an yttrium oxide coating are sequentially arranged on the inner surface of the carbon / carbon composite material crucible body, the glassy carbon coating has a high thermal matching degree with the crucible body, a good bonding effect, and can effectively prevent the escape of carbon in the crucible body; the surface of the pyrolytic carbon transition coating is a rough structure, and has a similar thermal expansion coefficient to the glassy carbon coating. Compared with the glassy carbon coating with a dense and smooth surface, the yttrium oxide coating prepared on the pyrolytic carbon transition coating can effectively improve the bonding effect of the coating; the yttrium oxide coating has excellent thermal stability, excellent resistance to silicon corrosion, and can ensure the purity of molten silicon in the process of pulling single crystals. In addition, the carbon / carbon composite crucible body is formed by a multi-layer structure preform through densification, and the multi-layer structure preform adopts an isotropic pure mesh tire needle-punched layer as the surface layer combined with the subsequent functional coating, which can improve the bonding effect with the subsequent functional layer, and adopts a carbon cloth / mesh tire laminated needle-punched layer combined with a carbon fiber winding layer as the external supporting structure of the pure mesh tire needle-punched layer, which provides mechanical support for the multi-layer structure preform as a whole, which can not only ensure the overall mechanical properties of the crucible, but also ensure a good bonding effect with the subsequent functional coating, thereby increasing the service life of the crucible.
[0007] The objectives of the present invention are achieved through the following technical solutions.
[0008] An integrated carbon / carbon composite material crucible containing three layers of composite coating, the crucible comprising a carbon / carbon composite material crucible body, a glassy carbon coating, a pyrolytic carbon transition coating and an yttrium oxide coating, the glassy carbon coating being in contact with the inner surface of the carbon / carbon composite material crucible body, and the pyrolytic carbon transition coating being located between the glassy carbon coating and the yttrium oxide coating;
[0009] The carbon / carbon composite material crucible body is prepared by carbon densification of a multi-layer structure preform; the multi-layer structure preform is a structure composed of a mesh needle-punched ply and a plurality of ply units superimposed on the outer surface of the mesh needle-punched ply, and the ply unit is composed of a carbon cloth / mesh laminated needle-punched ply formed by needle-punching and stitching a carbon fiber mesh layer and a carbon cloth layer, and a carbon fiber winding layer wound on the outer surface of the carbon cloth / mesh laminated needle-punched ply.
[0010] Furthermore, the thickness of the glassy carbon coating is 50 to 300 μm.
[0011] Furthermore, the thickness of the pyrolytic carbon transition coating is 10 to 100 μm.
[0012] Furthermore, the thickness of the yttrium oxide coating is 100-500 μm.
[0013] Furthermore, the density of the multilayer structure preform is 0.40-0.50 g / cm 3 The density of the carbon / carbon composite crucible body is 1.60-1.80 g / cm 3 .
[0014] Furthermore, the glassy carbon coating is prepared by a resin impregnation carbonization process, which specifically includes the following preparation steps:
[0015] The carbon / carbon composite material crucible body is first impregnated in resin, impregnated for 0.5 to 5 hours at an impregnation pressure of 1 to 3 MPa, then heated to 100 to 300° C. at a heating rate of 1 to 3° C. / h and cured at 100 to 300° C. for 3 to 5 hours, then heated to 900 to 1100° C. at a heating rate of 1 to 5° C. / h and carbonized at 900 to 1100° C. for 5 to 10 hours, thereby forming the glassy carbon coating on the inner surface of the carbon / carbon composite material crucible body;
[0016] The resin is preferably furfural resin or phenolic resin.
[0017] Furthermore, the pyrolytic carbon transition coating is prepared by a chemical vapor deposition process, which specifically includes the following preparation steps:
[0018] Propylene or natural gas is used as the carbon source gas, the flow rate of the carbon source gas is 10-50 L / min, the deposition temperature is 900-1100° C., and the total deposition time is 10-30 h.
[0019] Furthermore, the yttrium oxide coating is prepared by a plasma spraying process, and the process parameters of the plasma spraying include: the particle size of the yttrium oxide powder is 10 to 100 μm, the carrier gas (such as nitrogen) pressure is 0.2 to 3 MPa, the auxiliary gas (such as hydrogen) pressure is 0.1 to 2 MPa, the current is 300 to 900 A, the voltage is 40 to 120 V, and the spraying distance is 30 to 180 mm.
[0020] Furthermore, the multilayer structure preform is subjected to pyrolytic carbonization and resin carbonization treatment in sequence by using a chemical vapor infiltration process combined with a resin impregnation carbonization process, that is, the multilayer structure preform is first subjected to pyrolytic carbonization and densification to 1.0-1.20 g / cm 3 Then, the carbon fiber preform is subjected to resin carbon densification treatment by resin impregnation carbonization process and the density is increased to 1.60-1.80 g / cm 3 , then a carbon / carbon composite material crucible body is obtained;
[0021] Preferably, the parameters of the chemical vapor infiltration process are as follows: propylene or natural gas is used as the carbon source gas, the flow rate of the carbon source gas is 10-50 L / min, the deposition temperature is 900-1100°C, and the total deposition time is 100-140 h; the parameters of the resin impregnation carbonization process are as follows: furfural resin or phenolic resin is used as the impregnating agent, impregnated for 0.5-5 h at an impregnation pressure of 1.0-3.0 MPa, then cured at a curing temperature of 100-300°C for 1-10 h, and then carbonized at a carbonization temperature of 900-1000°C for 4-10 h, and the heating rate of the curing and carbonization process is 10-20°C / h.
[0022] Furthermore, the multilayer structure preform comprises the following specific preparation steps:
[0023] (1) laying a carbon fiber web on a core mold and performing acupuncture to form a web needle-punched layer;
[0024] (2) first laying a carbon cloth layer on the mesh needle-punched ply formed in step (1), then laying a carbon fiber mesh layer on the carbon cloth layer, and needle-punching and sewing the laid carbon fiber mesh layer and the carbon cloth layer to form a carbon cloth / mesh laminate needle-punched ply; finally, winding carbon fiber filaments on the carbon cloth / mesh laminate needle-punched ply to form a carbon fiber winding layer, and the carbon cloth / mesh laminate needle-punched ply and the carbon fiber winding layer constitute a ply unit;
[0025] (3) Repeating the operation of step (2) multiple times, stacking multiple ply units on the ply unit formed in step (2) until the desired thickness of the preform is reached (i.e., the surface of the carbon fiber winding layer formed in step (2) forms an alternating stacking structure of carbon cloth / net tire stacking needle punching ply and carbon fiber winding layer, until the desired thickness of the preform is reached after the last winding of carbon fiber filaments), then all ply units constitute an external support stack, and a preform precursor is obtained at this time;
[0026] (4) The preform precursor obtained in step (3) is heated to achieve a hardening effect, thereby obtaining the multilayer structure preform.
[0027] Furthermore, the carbon fiber mat is a thin felt made of chopped carbon fiber with a surface density of 50 to 500 g / m 2 .
[0028] Furthermore, the needle-punching density of the web needle-punched layer is 10 to 50 needles / cm 2 The acupuncture depth is 5 to 10 mm.
[0029] Furthermore, the thickness of the web needle-punched layer is 100 to 200 mm.
[0030] Furthermore, the surface density of the carbon cloth used to lay the carbon cloth layer is 200 to 800 g / m2 .
[0031] Furthermore, the needle-punching density of the carbon cloth / web layer is 10 to 50 needles / cm 2 The acupuncture depth is 5 to 10 mm.
[0032] Furthermore, the carbon fiber filaments in the carbon fiber winding layer are wound along a direction that is ±45° with respect to the axial direction of the preform.
[0033] Furthermore, according to the structure of the integrated crucible, from the upper part to the lower part of the crucible along its depth direction, it is divided into a crucible straight tube section, a crucible R-angle transition section, and a crucible bottom surface. Then, the thickness of the outer support laminate of the straight tube section of the crucible in the preform is less than the thickness of the outer support laminate of the crucible R-angle transition section, and the thickness of the outer support laminate of the crucible R-angle transition section is less than the thickness of the outer support laminate of the crucible bottom surface.
[0034] Furthermore, the thickness of the outer support stack of the crucible straight tube section, the crucible R angle transition section and the crucible bottom surface in the preform are 100-300 mm, 200-400 mm and 300-600 mm respectively.
[0035] Furthermore, the straight section of the crucible, the R-angle transition section of the crucible and the bottom surface of the crucible adopt laying units of different thicknesses to achieve different thicknesses of the external support stack in different areas. The thicknesses of the laying units adopted in the straight section of the crucible, the R-angle transition section of the crucible and the bottom surface of the crucible are 10-20 mm, 15-30 mm and 20-40 mm respectively, and the difference in thickness of the laying units in different areas is caused by the different thicknesses of the carbon cloth layer, that is, the thickness of the carbon cloth layer laid in the corresponding area of the crucible R-angle transition section and the bottom surface of the crucible is greater than the thickness of the carbon cloth layer laid in the corresponding area of the straight section of the crucible.
[0036] Furthermore, the specific laying operation of the lamination unit in the outer support stack is as follows: first, a whole carbon cloth is laid, and the carbon cloth layer of the straight section of the crucible is formed after the whole carbon cloth is laid, and the R-angle transition section of the crucible and the bottom of the crucible need to be stacked with carbon cloth of the required thickness in their corresponding areas on the basis of the whole carbon cloth laying, thus forming the carbon cloth layer of the R-angle transition section of the crucible and the carbon cloth layer of the bottom of the crucible; then, carbon fiber mesh tires are laid on the carbon cloth layers in three different areas, and needle-punched and sewed to form carbon cloth / mesh tire laminated needle-punched layers in three different areas; finally, carbon fiber filaments are continuously wound on the carbon cloth / mesh tire laminated needle-punched layers in three different areas to form a carbon fiber winding layer.
[0037] Furthermore, in step (4), the heating temperature is 80 to 200° C., and the heating time is 5 to 10 hours.
[0038] Beneficial effects:
[0039] (1) The present invention sequentially prepares a glassy carbon coating, a pyrolytic carbon transition coating and an yttrium oxide coating on the crucible body as a composite functional coating. The porosity of the glassy carbon coating is approximately zero, and the surface is more dense, which can effectively prevent the carbon from escaping from the crucible body. Moreover, the glassy carbon and the carbon in the crucible body are of the same substance, with a high thermal matching degree and a good bonding effect with the crucible body. However, the glassy carbon coating has a dense and smooth structure, and the bonding performance of the yttrium oxide coating with it is relatively weak, so the yttrium oxide coating is prone to falling off. The pyrolytic carbon coating is introduced between the glassy carbon coating and the yttrium oxide coating. On the one hand, the dense pyrolytic carbon coating can further prevent the carbon from escaping from the crucible body. At the same time, the pyrolytic carbon and the glassy carbon are both carbonaceous materials with similar thermal expansion coefficients. Therefore, the two have excellent bonding performance. On the other hand, the surface state of the pyrolytic carbon coating is a rough structure, and the yttrium oxide coating can be embedded in the surface of the pyrolytic carbon coating. The two have a strong bonding performance, thereby improving the problem of the yttrium oxide coating falling off easily. Yttrium oxide coating does not introduce impurities during the molten silicon process, meeting the requirements of crystal pulling. Moreover, the valence bond structure of yttrium oxide itself makes it difficult for silicon to enter the interior of yttrium oxide at high temperatures, and it has excellent resistance to silicon corrosion. In addition, compared with aluminum oxide coating, yttrium oxide coating has higher temperature resistance, and no phase change occurs at high temperatures, further increasing the stability of yttrium oxide coating.
[0040] (2) The multi-layer structure preform described in the present invention adopts a pure mesh needle-punched layer as the surface layer combined with the subsequent functional coating. Because the isotropic structure presented by the pure mesh needle-punched layer has a certain roughness and uniform surface quality, it is not only conducive to the preparation of the subsequent functional coating, but also improves the bonding performance between the functional coating and the crucible body, thereby effectively improving the service life of the crucible product; the external support structure composed of the carbon cloth / mesh laminated needle-punched layer and the carbon fiber winding layer has high strength, low density and thin thickness, and can provide good mechanical support for the multi-layer structure preform as a whole, meeting the requirements of the crucible product for mechanical properties.
[0041] (3) The resin impregnation carbonization process used in the present invention can meet the requirements of large-scale, batch-scale glassy carbon coating preparation. It should be noted that in the preparation of glassy carbon coating, the heating rate of the curing and carbonization process is an important factor affecting the density of the coating. If the heating rate is too fast, the glassy carbon coating will have defects such as microcracks and pores. If the heating rate is too slow, the production cost will be greatly increased.
[0042] (4) The present invention utilizes plasma spraying technology to prepare yttrium oxide coatings, which have controllable thickness, low porosity, high quality consistency, high preparation efficiency, and are suitable for mass production.
[0043] (5) Based on the structural characteristics of the crucible itself, it can be seen that the stress concentration is the greatest at the R corner, which is prone to fatigue cracks. Increasing the thickness here can effectively make the straight tube section transition smoothly to the bottom surface, reducing the stress concentration problem at the R corner; in addition, affected by the actual working conditions, the R corner and the bottom surface are most affected by the gravity of the silicon melt. Increasing the thickness of these two places can effectively prevent the occurrence of "silicon leakage"; and setting different thicknesses for different areas can effectively reduce the overall weight of the crucible product and reduce the manufacturing cost of the crucible product on the basis of ensuring the overall mechanical properties of the crucible product. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 Schematic diagram of the structure of the integrated carbon / carbon composite material crucible containing three layers of composite coating in Example 1.
[0045] Among them, 1-external support laminate, 2-mesh needle-punched laminate, 3-glass carbon coating, 4-pyrolytic carbon transition coating, 5-yttrium oxide coating. DETAILED DESCRIPTION
[0046] The present invention is further described below in conjunction with specific embodiments, wherein the methods are conventional methods unless otherwise specified, and the raw materials can be obtained from public commercial channels unless otherwise specified. In addition, in the description of the present invention, it should be understood that the orientations or positional relationships indicated by the terms "upper", "lower", "front", "back", "left", "right", "top", "bottom", "inside", "outside", etc. are based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation to the present invention.
[0047] Example 1
[0048] The integrated carbon / carbon composite material crucible containing three layers of composite coating comprises the following preparation steps:
[0049] (1) The surface density of the coating on the core is 50g / m 2 The carbon fiber web is needle-punched to form a web needle-punched layer 2 with a thickness of 100 mm;
[0050] The acupuncture density is 10 needles / cm 2 , the needle puncture depth is 5mm; the core mold is made according to the inner surface structure and size of the integrated crucible;
[0051] (2) First, use a sheet with a thickness of 5 mm and a surface density of 200 g / m 2The whole carbon cloth is laid on the mesh tire needle-punched layer 2. After laying a whole carbon cloth, the carbon cloth layer of the straight section of the crucible is formed, and the crucible R angle transition section needs to be superimposed with a layer of small carbon cloth with a thickness of 5mm on the basis of the whole carbon cloth layer to thicken the area to form the carbon cloth layer of the crucible R angle transition section, and the bottom surface of the crucible also needs to be superimposed with two layers of small carbon cloth with a thickness of 5mm on the basis of the whole carbon cloth layer to thicken the area to form the carbon cloth layer of the bottom surface of the crucible; then A carbon fiber mesh is laid on the carbon cloth layer in three different areas of the ferry section and the bottom of the crucible to form a carbon fiber mesh layer with a thickness of 4 mm, and then needle-punched and sewn, so that carbon cloth / mesh laminated needle-punched layers with thicknesses of 9 mm, 14 mm, and 19 mm are formed in the three different areas respectively; finally, carbon fiber filaments are continuously wound on the carbon cloth / mesh laminated needle-punched layers in the three different areas along a direction of ±45° with the axial direction of the preform to form a carbon fiber winding layer, and the thickness of the carbon fiber winding layer is 1 mm;
[0052] Among them, according to the structure of the integrated crucible, from the upper part to the lower part of the crucible along its depth direction, it is divided into a crucible straight section, a crucible R angle transition section, and a crucible bottom surface; the carbon cloth / net tire laminated needle-punched layer and the carbon fiber winding layer form a layer unit, and the thickness of the layer unit of the crucible straight section, the thickness of the layer unit of the crucible R angle transition section, and the thickness of the layer unit of the crucible bottom surface are 10mm, 15mm, and 20mm respectively; the needle density of the carbon cloth / net tire laminated needle-punched layer is 10 needles / cm 2 , the acupuncture depth is 5 mm;
[0053] (3) Repeating the operation of step (2) multiple times, forming an alternating stacking structure of carbon cloth / mesh laminated needle-punched layers followed by carbon fiber winding layers on the surface of the carbon fiber winding layer in step (2) (i.e., stacking multiple layer units on the layer units formed in step (2)), until the desired thickness of the preform is reached after the last winding of the carbon fiber filaments, thereby obtaining a preform precursor;
[0054] Among them, all the ply units stacked in sequence on the mesh needle-punched ply 2 constitute an outer support laminate 1 for supporting the mesh needle-punched ply 2, and the number of ply units laid in different areas is 15 layers. Then, the thickness of the outer support laminate 1 of the straight section of the crucible, the thickness of the outer support laminate 1 of the R-angle transition section of the crucible, and the thickness of the outer support laminate 1 of the bottom surface of the crucible are 150 mm, 225 mm, and 300 mm, respectively.
[0055] (4) The preform precursor obtained in step (3) is placed at 80° C. for 10 h to achieve a hardening effect, and a density of 0.40 g / cm 3 A multi-layer structure preform;
[0056] (5) First, the multilayer structure preform is subjected to pyrolytic carbon densification treatment using a chemical vapor infiltration process and the density is increased to 1.0 g / cm 3 Then, the carbon fiber preform is subjected to resin carbon densification treatment by resin impregnation carbonization process and the density is increased to 1.60g / cm 3 , then a carbon / carbon composite material crucible body is obtained;
[0057] The parameters of the chemical vapor infiltration process are as follows: propylene is used as the carbon source gas, the flow rate of the carbon source gas is 10 L / min, the deposition temperature is 900°C, and the total deposition time is 100 h;
[0058] The parameters of the resin impregnation carbonization process are as follows: furfural resin is used as the impregnating agent, impregnated at an impregnation pressure of 1.0 MPa for 0.5 h, then cured at a curing temperature of 100 °C for 1 h, and then carbonized at a carbonization temperature of 900 °C for 4 h. The heating rate of the curing and carbonization process is 10 °C / h;
[0059] (6) The carbon / carbon composite crucible body is first immersed in furfural resin, immersed for 0.5 h at an immersion pressure of 1.0 MPa, then heated to 100°C at a heating rate of 1°C / h and cured at 100°C for 3 h, and then heated to 900°C at a heating rate of 1°C / h and carbonized at 900°C for 5 h, thereby forming a glassy carbon coating 3 with a thickness of 50 μm on the inner surface of the carbon / carbon composite crucible body;
[0060] (7) preparing a pyrolytic carbon transition coating 4 with a thickness of 10 μm on the glassy carbon coating 3 by a chemical vapor deposition process;
[0061] The parameters of the chemical vapor deposition process are as follows: propylene is used as the carbon source gas, the flow rate of the carbon source gas is 10 L / min, the deposition temperature is 900 °C, and the total deposition time is 10 h;
[0062] (8) A yttrium oxide coating 5 with a thickness of 500 μm is prepared on the pyrolytic carbon transition coating 4 by a plasma spraying process, and the preparation of the crucible is completed accordingly, such as Figure 1 As shown;
[0063] The process parameters of plasma spraying include: the particle size of yttrium oxide powder is 100 μm, the pressure of carrier gas (such as nitrogen) is 3.0 MPa, the pressure of auxiliary gas (such as hydrogen) is 2.0 MPa, the current is 900 A, the voltage is 120 V, and the spraying distance is 30 mm.
[0064] The crucible prepared in this embodiment is used to pull silicon rods in a single crystal furnace, and the crucible coating is kept stable for 220 hours (crystal pulling is continued in the crucible. When the liquid level is stable and no bubbles overflow, it indicates that the coating is stable; when bubbles escape, it indicates that the coating is invalid). Within the crucible coating stability time range, the carbon content and oxygen content of the silicon wafer after cutting are tested to verify the carbon barrier performance and purity performance of the crucible. According to the test results, the carbon content is 8.34×10 16 atoms / cm 3 , oxygen content is 1.48×10 17 atoms / cm 3 .
[0065] Example 2
[0066] The integrated carbon / carbon composite material crucible containing three layers of composite coating comprises the following preparation steps:
[0067] (1) Lay the surface density on the core mold at 300g / m 2 The carbon fiber mesh is needle-punched to form a mesh needle-punched layer 2 with a thickness of 150 mm;
[0068] The acupuncture density is 30 needles / cm 2 , the needle puncture depth is 8mm; the core mold is made according to the inner surface structure and size of the integrated crucible;
[0069] (2) First, use a sheet with a thickness of 8 mm and a surface density of 500 g / m 2 The whole carbon cloth is laid on the mesh tire needle-punched layer 2. After laying a whole carbon cloth, the carbon cloth layer of the straight section of the crucible is formed, and the R-angle transition section of the crucible needs to be superimposed with a layer of small carbon cloth with a thickness of 8mm on the basis of the whole carbon cloth layer to thicken the area to form the carbon cloth layer of the R-angle transition section of the crucible, and the bottom surface of the crucible also needs to be superimposed with two layers of small carbon cloth with a thickness of 8mm on the basis of the whole carbon cloth layer to thicken the area to form the carbon cloth layer of the bottom surface of the crucible; then A carbon fiber mesh is laid on the carbon cloth layer in three different areas of the ferry section and the bottom of the crucible to form a carbon fiber mesh layer with a thickness of 6 mm, and then needle-punched and sewn, so that carbon cloth / mesh laminated needle-punched layers with thicknesses of 14 mm, 22 mm, and 30 mm are formed in the three different areas respectively; finally, carbon fiber yarns are continuously wound on the carbon cloth / mesh laminated needle-punched layers in the three different areas along a direction of ±45° with the axial direction of the preform to form a carbon fiber winding layer, and the thickness of the carbon fiber winding layer is 1 mm;
[0070] Among them, according to the structure of the integrated crucible, from the upper part to the lower part of the crucible along its depth direction, it is divided into a crucible straight section, a crucible R angle transition section, and a crucible bottom surface; the carbon cloth / net tire laminated needle-punched layer and the carbon fiber winding layer form a layer unit, and the thickness of the layer unit of the crucible straight section, the thickness of the layer unit of the crucible R angle transition section, and the thickness of the layer unit of the crucible bottom surface are 15mm, 23mm, and 31mm respectively; the needle density of the carbon cloth / net tire laminated needle-punched layer is 20 needles / cm 2 , the acupuncture depth is 8 mm;
[0071] (3) Repeating the operation of step (2) multiple times, forming an alternating stacking structure of carbon cloth / mesh laminated needle-punched layers followed by carbon fiber winding layers on the surface of the carbon fiber winding layer in step (2) (i.e., stacking multiple layer units on the layer units formed in step (2)), until the desired thickness of the preform is reached after the last winding of the carbon fiber filaments, thereby obtaining a preform precursor;
[0072] Among them, all the ply units stacked in sequence on the mesh needle-punched ply 2 constitute an outer support laminate 1 for supporting the mesh needle-punched ply 2, and the number of ply units laid in different areas is 16 layers. The thickness of the outer support laminate 1 of the straight tube section of the crucible, the thickness of the outer support laminate 1 of the R-angle transition section of the crucible, and the thickness of the outer support laminate 1 of the bottom surface of the crucible are 240 mm, 368 mm, and 496 mm, respectively.
[0073] (4) The preform precursor obtained in step (3) was placed at 150° C. for 8 h to achieve a hardening effect, and a density of 0.46 g / cm 3 A multi-layer structure preform;
[0074] (5) First, the multilayer structure preform is subjected to pyrolytic carbon densification treatment using a chemical vapor infiltration process and the density is increased to 1.10 g / cm 3 Then, the carbon fiber preform is subjected to resin carbon densification treatment by resin impregnation carbonization process and the density is increased to 1.70g / cm 3 , then a carbon / carbon composite material crucible body is obtained;
[0075] The parameters of the chemical vapor infiltration process are as follows: propylene is used as the carbon source gas, the flow rate of the carbon source gas is 30 L / min, the deposition temperature is 1000°C, and the total deposition time is 120 h;
[0076] The parameters of the resin impregnation carbonization process are as follows: furfural resin is used as the impregnation agent, impregnation is carried out for 3 h at an impregnation pressure of 2.0 MPa, then curing is carried out for 6 h at a curing temperature of 200 °C, and then carbonization is carried out for 7 h at a carbonization temperature of 950 °C. The heating rate of the curing and carbonization process is 15 °C / h.
[0077] (6) The carbon / carbon composite crucible body is first immersed in phenolic resin at an immersion pressure of 2.0 MPa for 1.5 h, then heated to 200°C at a heating rate of 2°C / h and cured at 200°C for 4 h, then heated to 1000°C at a heating rate of 3°C / h and carbonized at 1000°C for 7 h, thereby forming a glassy carbon coating 3 with a thickness of 180 μm on the inner surface of the carbon / carbon composite crucible body;
[0078] (7) preparing a pyrolytic carbon transition coating 4 with a thickness of 60 μm on the glassy carbon coating 3 by a chemical vapor deposition process;
[0079] The parameters of the chemical vapor deposition process are as follows: natural gas is used as the carbon source gas, the flow rate of the carbon source gas is 30 L / min, the deposition temperature is 1000 °C, and the total deposition time is 20 h;
[0080] (8) preparing a yttrium oxide coating 5 with a thickness of 300 μm on the pyrolytic carbon transition coating 4 by a plasma spraying process, and completing the preparation of the crucible accordingly;
[0081] Among them, the process parameters of plasma spraying include: the particle size of yttrium oxide powder is 55μm, the carrier gas (such as nitrogen) pressure is 1.8MPa, the auxiliary gas (such as hydrogen) pressure is 1.0MPa, the current is 600A, the voltage is 80V, and the spraying distance is 100mm.
[0082] The crucible prepared in this embodiment is used to pull silicon rods in a single crystal furnace, and the crucible coating is kept stable for 180 hours (crystal pulling is continued in the crucible. When the liquid level is stable and no bubbles overflow, it indicates that the coating is stable; when bubbles escape, it indicates that the coating is invalid). Within the crucible coating stability time range, the carbon content and oxygen content of the silicon wafer after cutting are tested to verify the carbon barrier performance and purity performance of the crucible. According to the test results, the carbon content is 12.90×10 16 atoms / cm 3 , oxygen content is 2.04×10 17 atoms / cm 3 .
[0083] Example 3
[0084] The integrated carbon / carbon composite material crucible containing three layers of composite coating comprises the following preparation steps:
[0085] (1) Lay the surface density on the core mold with 500g / m 2 The carbon fiber mesh is needle-punched to form a mesh needle-punched layer 2 with a thickness of 200 mm;
[0086] The acupuncture density is 50 needles / cm 2, the needle puncture depth is 10mm; the core mold is made according to the inner surface structure and size of the integrated crucible;
[0087] (2) First, use a sheet with a thickness of 10 mm and a surface density of 800 g / m 2 The whole carbon cloth is laid on the mesh tire needle-punched layer 2. After laying a whole carbon cloth, the carbon cloth layer of the straight section of the crucible is formed, and the crucible R angle transition section needs to be superimposed with a layer of small carbon cloth with a thickness of 10mm on the basis of the whole carbon cloth layer to thicken the area to form the carbon cloth layer of the crucible R angle transition section, and the bottom surface of the crucible also needs to be superimposed with two layers of small carbon cloth with a thickness of 10mm on the basis of the whole carbon cloth layer to thicken the area to form the carbon cloth layer of the bottom surface of the crucible; then A carbon fiber mesh is laid on the carbon cloth layer in the transition section and the three different areas of the bottom surface of the crucible to form a carbon fiber mesh layer with a thickness of 8 mm, and then needle-punched and sewn, so that carbon cloth / mesh laminated needle-punched layers with thicknesses of 18 mm, 28 mm, and 38 mm are formed in the three different areas respectively; finally, carbon fiber yarns are continuously wound on the carbon cloth / mesh laminated needle-punched layers in the three different areas along a direction of ±45° with the axial direction of the preform to form a carbon fiber winding layer, and the thickness of the carbon fiber winding layer is 2 mm;
[0088] Among them, according to the structure of the integrated crucible, from the upper part to the lower part of the crucible along its depth direction, it is divided into a crucible straight section, a crucible R angle transition section, and a crucible bottom surface; the carbon cloth / net tire laminated needle-punched layer and the carbon fiber winding layer form a layer unit, and the thickness of the layer unit of the crucible straight section, the thickness of the layer unit of the crucible R angle transition section, and the thickness of the layer unit of the crucible bottom surface are 20mm, 30mm, and 40mm respectively; the needle density of the carbon cloth / net tire laminated needle-punched layer is 50 needles / cm 2 , the acupuncture depth is 10 mm;
[0089] (3) Repeating the operation of step (2) multiple times, forming an alternating stacking structure of carbon cloth / mesh laminated needle-punched layers followed by carbon fiber winding layers on the surface of the carbon fiber winding layer in step (2) (i.e., stacking multiple layer units on the layer units formed in step (2)), until the desired thickness of the preform is reached after the last winding of the carbon fiber filaments, thereby obtaining a preform precursor;
[0090] Among them, all the ply units stacked in sequence on the mesh needle-punched ply 2 constitute an outer support laminate 1 for supporting the mesh needle-punched ply 2, and the number of ply units laid in different areas is 13 layers. The thickness of the outer support laminate 1 of the straight section of the crucible, the thickness of the outer support laminate 1 of the R-angle transition section of the crucible, and the thickness of the outer support laminate 1 of the bottom surface of the crucible are 260 mm, 390 mm, and 520 mm, respectively.
[0091] (4) The preform precursor obtained in step (3) was placed at 200°C for 5 hours to achieve a hardening effect, and a density of 0.50 g / cm 3 A multi-layer structure preform;
[0092] (5) First, the multilayer structure preform is subjected to pyrolytic carbon densification treatment using a chemical vapor infiltration process and the density is increased to 1.20 g / cm 3 Then, the carbon fiber preform is subjected to resin carbon densification treatment by resin impregnation carbonization process and the density is increased to 1.80g / cm 3 , then a carbon / carbon composite material crucible body is obtained;
[0093] The parameters of the chemical vapor infiltration process are as follows: propylene is used as the carbon source gas, the flow rate of the carbon source gas is 50 L / min, the deposition temperature is 1100°C, and the total deposition time is 140 h;
[0094] The parameters of the resin impregnation carbonization process are as follows: furfural resin is used as the impregnating agent, impregnated at an impregnation pressure of 3.0 MPa for 5 h, then cured at a curing temperature of 300 °C for 10 h, and then carbonized at a carbonization temperature of 1000 °C for 10 h. The heating rate of the curing and carbonization process is 20 °C / h;
[0095] (6) The carbon / carbon composite crucible body is first immersed in phenolic resin at an immersion pressure of 3.0 MPa for 2 h, then heated to 300°C at a heating rate of 3°C / h and cured at 300°C for 5 h, then heated to 1100°C at a heating rate of 5°C / h and carbonized at 1100°C for 10 h, thereby forming a glassy carbon coating 3 with a thickness of 300 μm on the inner surface of the carbon / carbon composite crucible body;
[0096] (7) preparing a pyrolytic carbon transition coating 4 with a thickness of 100 μm on the glassy carbon coating 3 by a chemical vapor deposition process;
[0097] The parameters of the chemical vapor deposition process are as follows: natural gas is used as the carbon source gas, the flow rate of the carbon source gas is 50 L / min, the deposition temperature is 1100 °C, and the total deposition time is 30 h;
[0098] (8) preparing a yttrium oxide coating 5 with a thickness of 100 μm on the pyrolytic carbon transition coating 4 by a plasma spraying process, and completing the preparation of the crucible accordingly;
[0099] Among them, the process parameters of plasma spraying include: the particle size of yttrium oxide powder is 10μm, the carrier gas (such as nitrogen) pressure is 0.2MPa, the auxiliary gas (such as hydrogen) pressure is 0.1MPa, the current is 300A, the voltage is 40V, and the spraying distance is 180mm.
[0100] The crucible prepared in this embodiment is used to pull silicon rods in a single crystal furnace, and the crucible coating is kept stable for 150 hours (crystal pulling is continued in the crucible. When the liquid level is stable and no bubbles overflow, it indicates that the coating is stable; when bubbles escape, it indicates that the coating is invalid). Within the crucible coating stability time range, the carbon content and oxygen content of the silicon wafer after cutting are tested to verify the carbon barrier performance and purity performance of the crucible. According to the test results, the carbon content is 24.67×10 16 atoms / cm 3 , oxygen content is 3.16×10 17 atoms / cm 3 .
[0101] Comparative Example 1
[0102] On the basis of Example 1, only the process of preparing the pyrolytic carbon transition coating 4 on the glassy carbon coating 3 in step (7) is omitted. That is, the yttrium oxide coating 5 is directly prepared on the glassy carbon coating 3 according to the process conditions of step (8). The other steps and preparation conditions are the same as those in Example 1, and accordingly an integrated carbon / carbon composite material crucible without the pyrolytic carbon transition coating 4 is obtained.
[0103] The crucible prepared in Comparative Example 1 was used to pull silicon rods in a single crystal furnace, and the crucible coating was kept stable for 180 hours (crystal pulling was continued in the crucible. When the liquid level was stable and no bubbles overflowed, it indicated that the coating was stable; when bubbles escaped, it indicated that the coating failed). Within the crucible coating stability time range, the carbon content and oxygen content of the silicon wafer after cutting were tested to verify the carbon barrier performance and purity performance of the crucible. According to the test results, the carbon content was 13.52×10 16 atoms / cm 3 , oxygen content is 1.56×10 17 atoms / cm 3 .
[0104] In summary, the above are only preferred embodiments of the present invention and are not intended to limit the protection scope of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. An integrated carbon / carbon composite material crucible with three layers of composite coating, characterized in that: The crucible comprises a carbon / carbon composite crucible body, a glassy carbon coating, a pyrolytic carbon transition coating and an yttrium oxide coating, wherein the glassy carbon coating contacts the inner surface of the carbon / carbon composite crucible body, and the pyrolytic carbon transition coating is located between the glassy carbon coating and the yttrium oxide coating; The carbon / carbon composite material crucible body is prepared by carbon densification of a multi-layer structure preform; the multi-layer structure preform is a structure composed of a mesh needle-punched ply and a plurality of ply units superimposed on the outer surface of the mesh needle-punched ply, and the ply unit is composed of a carbon cloth / mesh laminated needle-punched ply formed by needle-punching and stitching a carbon fiber mesh layer and a carbon cloth layer, and a carbon fiber winding layer wound on the outer surface of the carbon cloth / mesh laminated needle-punched ply.
2. The integrated carbon / carbon composite material crucible containing three-layer composite coating according to claim 1, characterized in that: The thickness of the glassy carbon coating is 50 to 300 μm; Or / and, the thickness of the pyrolytic carbon transition coating is 10 to 100 μm; Or / and, the thickness of the yttrium oxide coating is 100-500 μm.
3. The integrated carbon / carbon composite material crucible containing three-layer composite coating according to claim 1 or 2, characterized in that: The density of the multilayer structure preform is 0.40-0.50 g / cm 3 The density of the carbon / carbon composite crucible body is 1.60-1.80 g / cm 3 .
4. The integrated carbon / carbon composite material crucible containing three-layer composite coating according to claim 1 or 2, characterized in that: The glassy carbon coating is prepared by a resin impregnation carbonization process, which specifically includes the following preparation steps: firstly immersing a carbon / carbon composite material crucible body in a resin, immersing for 0.5 to 5 hours at an impregnation pressure of 1 to 3 MPa, then heating to 100 to 300° C. at a heating rate of 1 to 3° C. / h and curing at 100 to 300° C. for 3 to 5 hours, then heating to 900 to 1100° C. at a heating rate of 1 to 5° C. / h and carbonizing at 900 to 1100° C. for 5 to 10 hours, thereby forming the glassy carbon coating on the inner surface of the carbon / carbon composite material crucible body; Or / and, the pyrolytic carbon transition coating is prepared by chemical vapor deposition process, which specifically includes the following preparation steps: using propylene or natural gas as carbon source gas, the flow rate of carbon source gas is 10-50L / min, the deposition temperature is 900-1100°C, and the total deposition time is 10-30h; Or / and, the yttrium oxide coating is prepared by a plasma spraying process, the process parameters of the plasma spraying include: the particle size of the yttrium oxide powder is 10 to 100 μm, the carrier gas pressure is 0.2 to 3 MPa, the auxiliary gas pressure is 0.1 to 2 MPa, the current is 300 to 900 A, the voltage is 40 to 120 V, and the spraying distance is 30 to 180 mm.
5. The integrated carbon / carbon composite material crucible with three-layer composite coating according to claim 3, characterized in that: First, the multilayer structure preform is subjected to pyrolytic carbon densification treatment by chemical vapor infiltration process and the density is increased to 1.0-1.20 g / cm 3 Then, the carbon fiber preform is subjected to resin carbon densification treatment by resin impregnation carbonization process and the density is increased to 1.60-1.80 g / cm 3 , then a carbon / carbon composite material crucible body is obtained.
6. The integrated carbon / carbon composite material crucible with three-layer composite coating according to claim 1, characterized in that: The multilayer structure preform comprises the following specific preparation steps: (1) laying a carbon fiber web on a core mold and performing acupuncture to form a web needle-punched layer; (2) first laying a carbon cloth layer on the mesh needle-punched ply formed in step (1), then laying a carbon fiber mesh layer on the carbon cloth layer, and needle-punching and sewing the laid carbon fiber mesh layer and the carbon cloth layer to form a carbon cloth / mesh laminate needle-punched ply; finally, winding carbon fiber filaments on the carbon cloth / mesh laminate needle-punched ply to form a carbon fiber winding layer, and the carbon cloth / mesh laminate needle-punched ply and the carbon fiber winding layer constitute a ply unit; (3) Repeating the operation of step (2) multiple times, stacking multiple ply units on the ply unit formed in step (2) until the required thickness of the preform is reached, and all the ply units constitute an external support stack, thereby obtaining a preform precursor; (4) The preform precursor obtained in step (3) is heated to achieve a hardening effect, thereby obtaining the multilayer structure preform.
7. The integrated carbon / carbon composite material crucible with three-layer composite coating according to claim 6, characterized in that: The carbon fiber mat is a thin felt made of chopped carbon fiber with a surface density of 50 to 500 g / m 2 ; Or / and, the needle-punching density of the web needle-punched layer is 10 to 50 needles / cm 2 , the acupuncture depth is 5 to 10 mm; Or / and, the thickness of the web needle-punched layer is 100-200 mm; or / and, the surface density of the carbon cloth used for laying the carbon cloth layer is 200 to 800 g / m 2 ; Or / and, the needle-punching density of the carbon cloth / net tire laminated needle-punching layer is 10 to 50 needles / cm 2 The acupuncture depth is 5 to 10 mm.
8. The integrated carbon / carbon composite material crucible with three-layer composite coating according to claim 6 or 7, characterized in that: According to the structure of the integrated crucible, the crucible is divided into a straight section of the crucible, a R-angle transition section of the crucible, and a bottom surface of the crucible in sequence along its depth direction from the upper part to the lower part. The thickness of the outer support laminate of the straight section of the crucible in the preform is less than the thickness of the outer support laminate of the R-angle transition section of the crucible, the thickness of the outer support laminate of the R-angle transition section of the crucible is less than the thickness of the outer support laminate of the bottom surface of the crucible, and the thickness of the outer support laminate of the straight section of the crucible, the R-angle transition section of the crucible, and the bottom surface of the crucible are 100-300 mm, 200-400 mm, and 300-600 mm, respectively.
9. The integrated carbon / carbon composite material crucible with three-layer composite coating according to claim 8, characterized in that: The straight section of the crucible, the R-angle transition section of the crucible and the bottom surface of the crucible use laying units of different thicknesses to achieve different thicknesses of the external support stack in different areas. The thicknesses of the laying units used in the straight section of the crucible, the R-angle transition section of the crucible and the bottom surface of the crucible are 10-20 mm, 15-30 mm, and 20-40 mm, respectively, and the difference in thickness of the laying units in different areas is caused by the different thicknesses of the carbon cloth layer.
10. The integrated carbon / carbon composite material crucible with three-layer composite coating according to claim 6 or 7, characterized in that: The heating temperature in step (4) is 80 to 200° C. and the heating time is 5 to 10 hours.
Citation Information
Patent Citations
Crucible and preparation method thereof
CN103102170A